'That Will Do': Logics of Deontic Necessity and Sufficiency. - Putte, Frederik (Erkenntnis, 2017)
We study a logic for deontic necessity and sufficiency (often interpreted as obligation, resp. strong permission), as originally proposed in van Benthem (Bull Sect Log 8(1):36-41, 1979). Building on earlier work in modal logic, we provide a sound and complete axiomatization for it, consider some standard extensions, and study other important properties. After that, we compare this logic to the logic of 'obligation as weakest permission' from Anglberger et al. (Rev Symb Log 8(4):807-827, 2015).